PENGARUH KEMASAN DAN HARGA PADA KEPUTUSAN PEMBELIAN MINUMAN ISOTONIK - NANDA RESMI; TRI WISMIARSI (Program Studi Magister Manajemen FE Unsri, 2015)
This study aimed to determine the effect of packaging and pricing on purchase decision of isotonic drinks. Variable of packaging was limited to structural elements, as these elements were getting less attention by previous research. Data were obtained from 261 employees and students in South Jakarta, using structured questionnaires. The questionnaires was developed based on research instruments from former research. The study used purposive sampling technique. Results from regression analysis showed that packaging and the price were significantly related to the purchase decision. The price effect was greater than the product packaging. The results also showed that there were significant differences in the variance of packaging, pricing, and purchase decisions based on groups of age, education level, the brand chosen, the intensity of purchase, and the place of purchase.